2007
DOI: 10.1063/1.2793687
|View full text |Cite
|
Sign up to set email alerts
|

Ge ∕ Si heteronanocrystal floating gate memory

Abstract: Metal oxide semiconductor field effect transistor memories with Ge∕Si heteronanocrystals (HNCs) as floating gate were fabricated and characterized. Ge∕Si HNCs with density of 5×1011cm−2 were grown on n-type Si (100) substrate with thin tunnel oxide on the top. Enhanced device performances including longer retention time, faster programming speed, and higher charge storage capability are demonstrated compared with Si nanocrystal (NC) memories. The erasing speed and endurance performance of Ge∕Si HNC memories ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Because only direct tunneling is used during writing/erasing operations, low power consumption and high endurance could be achieved. Huang et al reported the improvement of long-term retention of the nitrided Si NC memory, where SiN x /Si NC forms a staircase barrier [8].…”
Section: Direct Tunneling Oxidementioning
confidence: 99%
“…Because only direct tunneling is used during writing/erasing operations, low power consumption and high endurance could be achieved. Huang et al reported the improvement of long-term retention of the nitrided Si NC memory, where SiN x /Si NC forms a staircase barrier [8].…”
Section: Direct Tunneling Oxidementioning
confidence: 99%
“…6,7 Other novel structures such as double stack of nanocrystals, 8 engineered dielectric tunneling layers, 9,10 and heteronanocrystals 11,12 are also reported with good memory performance. Metal nanocrystal memory has the advantages over semiconductor counterparts in terms of higher density of states around the Fermi level, which is normally aligned in the forbidden gap of Si, leading to larger memory window and stronger coupling between the nanocrystals and the substrate for faster programming.…”
Section: Introductionmentioning
confidence: 95%
“…In addition, high-κ dielectrics were introduced in NC memory to shrink the equivalent tunnel oxide thickness and reduce the interpoly leakage current [13]. Recently, we reported the fabrication of Ge/Si heteronanocrystals (HNCs) and their applications in nonvolatile memories [14]. The goal was to further improve the retention performance achieved in Si NC memory, without compromising the programming efficiency.…”
Section: Introductionmentioning
confidence: 99%